Development Of Smart pH Prototype with FTTH Network Integration for Smart Chemistry Laboratory - Dzikri Danuarteu, Muhamad; Fauzi, Ahmad (Informatics Department-Universitas Dr. Soetomo, 2024)
Chemistry laboratories at the secondary education level have a vital role in supporting learning and research. However, manual management often faces obstacles in efficiency, accuracy, and data accessibility. Following the Regulation of the Minister of National Education Number 24 of 2007, pH meters are mandatory equipment in high school chemistry laboratories. However, conventional tools are often inadequate for precise real-time measurements. This study developed a Smart pH system integrating the Internet of Things (IoT) and fiber-to-the-home (FTTH) technology for real-time pH measurement. This system was designed using a pH-4502C sensor, Arduino Uno, NodeMCU ESP8266, and Arduino Cloud and tested on five types of solutions relevant to the high school chemistry curriculum, including salt solution, vinegar, lime, liquid soap, and mineral water. The test results showed an average accuracy of 99% and a 1-1.6 seconds data transmission delay. The total loss of the FTTH network was 3.65 dB, within the ITU-T G.984 standard limit. This research supports the fulfillment of national standards and improves the efficiency and reliability of pH measurements, opening up opportunities for further innovation in chemistry education laboratory automation in Indonesia.